The requirements for merging children of simple intellectual disabilities (learnable) with their ordinary peers in primary schools from the viewpoint of teachers and school administrations. (Journal of the College of Basic Education, 2022)
This research acquires its importance in an attraction with ordinary peers that would make negative change prevalent in society (according to studies) of their disability in learning. The research problem is summarized by the following question: What are the difficulties that hinder the application of the experience of integrating them with their ordinary peers in regular schools from the viewpoint of teachers and primary school headmasters? therefor of the research problem and its importance, the researcher formulated the aim of his research, which is: To identify the requirements for integrating members of this category into regular schools. The research sample consisted of (141) teachers in the primary schools in Karbala. To achieve the aims of the research, the researcher constructed a research instrument, and verified the availability of psychometric properties . The instrument consists of (28) items in its final form, divided into four fields equally. The statistical treatment of the data was carried out through getting (spss) . The results were shown: the lack of the necessary infrastructure to implement this project ,therefor of the results, the researcher has presented a number of recommendations. The most important one is concluded with a number of recommendation is that it is necessary to present clear.